Islamic Religious Education Learning Methods for Special Needs Children at Special Schools - Rosita, Rosita; Malihah, Noor; Fauzan, Umar (Southeast Asian Journal of Islamic Education, 2023)
This research provides a comprehensive analysis of the learning methods of Islamic religious education (PAI) for children with special needs (ABK) at special schools (SLB). Through a literature review, this research collected and analyzed three primary studies that focused on PAI learning methods for children with special needs, published in 2021-2022. These three studies highlight the diverse range of PAI teaching methods for children with special needs, including lectures, discussions, questions and answers, demonstrations, bandongan, sorongan, and repetition. The analysis reveals the positive impact of these methods on understanding the material and student learning achievement. However, the research also identifies significant obstacles in implementing the method, including students' adjustment to the method and limited teacher knowledge. To address these, learning methods need to be more sensitive to students' individual needs and improve teachers' quality through training and mentoring. This research offers valuable insights into the development of Islamic religious education for children with special needs at special schools, proposing several practical learning methods that can enhance the teaching and learning process, namely methods of love, advice, exemplary, listening, habituation, attention/supervision, motivation, character building, training/drilling, and wisdom methods. These methods aim to boost the child's self-confidence and reduce complaints and sadness, thereby improving their overall learning experience.